Global Research Trends on Student-Centered Learning in Schools: A Decade of Bibliometric Analysis Using R-Biblioshiny - Mariano Dos Santos (International Journal of Multidisciplinary Approach Research and Science, 2026)
This study conducted a bibliometric analysis of global research trends on student-centered learning (SCL) in schools over the past decade (2014–2024), using R-Biblioshiny and VoS Viewer software. The purpose of this study was to map the development of SCL research, identify the most productive authors and institutions, and explore dominant emerging themes in the literature. The analysis revealed a significant increase in SCL publications starting in 2018, with a primary focus on 21st-century skills such as critical thinking, creativity, collaboration, and communication. The Journal of Chemical Education was the primary publication source, with authors and institutions such as Dolezal D and Yogyakarta State University making particularly prolific contributions. Thematic mapping revealed that topics such as problem-solving and collaborative learning remained dominant, but there was a decline in the popularity of SCL and e-learning. These findings provide important insights for educational researchers and practitioners in designing more adaptive and inclusive learning strategies in the global era.